Research on ecological restoration and green reclamation technology of goaf in phosphorus mines - Hou, Di; Xu, Mengchao; Wang, Menglai; Li, Xiaoshuang; Li, Shujian; Wang, Jiawen; Cao, Mengzhen (Frontiers in Environmental Science, 2024)
The subsidiary of Yunnan Phosphate Group Co., Ltd., Kunyang Phosphate Mine's mining area is the subject of study. The mining of open-pit phosphate mines has caused significant damage to the ecological environment. Therefore, carrying out ecological restoration and green reclamation of the ecosystem in the mining area has become the top priority for current development.This article establishes an evaluation system for ecological restoration indicators, selecting four indicators including vegetation coverage, soil and water conservation, restoration of native plants, and plant species diversity to assess the effects of ecological restoration and green reclamation of phosphate mines..The techniques of reconstructing soil ecological structure using phosphate tailings substrate and improving acidic soil with soil conditioner and calcium-magnesium phosphate compound fertilizer were applied. A series of other measures were taken, including: drafting scientific ecological restoration plans; employing physical, chemical, and biological methods for ecological restoration and green reclamation; selecting suitable plant species for planting; enhancing planting techniques; and strengthening post-restoration ecological monitoring and regulation.